Life-threatening piperacillin-induced immune haemolysis in a patient with cystic fibrosis. (4th January 2013) - Marik, Paul Ellis; Parekh, Parth
Abstract : We present a 24-year-old man with a history significant for cystic fibrosis and insulin-dependent diabetes mellitus who developed anaemia in the setting of piperacillin-induced immune haemolysis. This case provided a diagnostic challenge, a rare association of piperacillin-induced haemolysis in those suffering from cystic fibrosis.